Mechanistic analysis of TBM cutterhead-ground interaction under mud build-up effect - Wang, Renchong; Li, Shiwei; Li, Congshi; Bian, Ke; Zhang, Jingxi (Frontiers in Earth Science, 2025)
IntroductionIn tunnel construction using TBMs, the complex mineral composition of strata and hydrogeological conditions often induce cutterhead mud build-up, which results in sharp increases in torque and thrust, thereby reducing excavation efficiency. Understanding the interaction between the TBM cutterhead and the surrounding ground under cutterhead blockage conditions is therefore a critical challenge for improving tunnelling efficiency.MethodsThis study develops a cutterhead load model that explicitly incorporates both aperture ratio and mud coating effects, and establishes a load-prediction framework for TBM excavation in composite strata.ResultsThe validity of the proposed model is verified using field monitoring data. On this basis, the influence of aperture ratio on excavation loads is systematically analysed.DiscussionAn optimization strategy—maintaining a relatively large aperture ratio—is proposed to enhance TBM tunnelling efficiency, providing effective theoretical support and practical guidance for addressing cutterhead mud build-up.